Communication strategy in socialising services for handling violence against women and children - Siska Mardiana; Annisarizki; Liza Diniarizky Putri; Sigit Surahman (Faculty of Communications Science, Dr. Soetomo University, 2025)
Cases of violence against children and women remain a worrying problem, but not all victims are willing to report it for various reasons. This situation has prompted the government to provide services through the Regional Technical Implementation Unit for the Protection of Women and Children. The purpose of this study is to analyse the effectiveness of the communication strategies used by the Regional Technical Implementation Unit for the Protection of Women and Children in Cilegon City in disseminating information about the services it provides. This research was conducted using a qualitative approach with a case study method. The informants consisted of five people based on purposive sampling techniques. Data collection was carried out through observation, interviews, and documentation, followed by data validity checking and data analysis. The results showed that the communication strategies used in disseminating information about services for handling violence against women and children included situation analysis and target determination, selection of communicators, selection of media, and preparation of media to be used as communication channels, and were implemented in various forms of socialisation activities, including psychoeducation activities, socialisation to schools in the form of distributing roll-up banners or seminars, and socialisation about the PATBM (Integrated Child Protection Community) programme at the village and sub-district levels. This strategy has been effective in expanding the dissemination of information about violence response services in the community. The study provides practical recommendations for public relations practitioners and offers directions for further research on communication strategies.